Mapping quantitative trait loci responsible for resistance to sheath blight in rice - Liu, G; Jia, Y; Correa Victoria, Fernando J.; Prado Patiño, Gustavo A.; Yeater, KM; McClung, AM; Correll, James C. (Scientific Societies, 2009)
Rice sheath blight (ShB), caused by the soilborne pathogen Rhizoctonia solani, annually causes severe losses in yield and quality in many rice production areas worldwide. Jasmine 85 is an indica cultivar that has proven to have a high level of resistance to this pathogen. The objective of this study was to determine the ability of controlled environment inoculation assays to detect ShB resistance quantitative trait loci (QTLs) in a cross derived from the susceptible cv. Lemont and the resistant cv. Jasmine 85. The disease reactions of 250 F5 recombinant inbred lines (RILs) were measured on the seedlings inoculated using microchamber and mist-chamber assays under greenhouse conditions. In total, 10 ShBQTLs were identified on chromosomes 1, 2, 3, 5, 6, and 9 using these two methods. The microchamber method identified four of five new ShBQTLs, one on each of chromosomes 1, 3, 5, and 6. Both microchamber and mist-chamber methods identified two ShB-QTLs, qShB1 and qShB9- 2. Four of the ShB-QTLs or ShB-QTL regions identified on chromosomes 2, 3, and 9 were previously reported in the literature. The major ShB-QTL qShB9-2, which cosegregated with simple sequence repeat (SSR) marker RM245 on chromosome 9, contributed to 24.3 and 27.2% of total phenotypic variation in ShB using microchamber and mistchamber assays, respectively. qShB9-2, a plant-stage-independent QTL, was also verified in nine haplotypes of 10 resistant Lemont/Jasmine 85 RILs using haplotype analysis. These results suggest that multiple ShBQTLs are involved in ShB resistance and that microchamber and mistchamber methods are effective for detecting plant-stage-independent QTLs. Furthermore, two SSR markers, RM215 and RM245, are robust markers and can be used in marker-assisted breeding programs to improve ShB resistance.